Determinants of physical activity among female students based on the transtheoretical model - Maryam Abdoli; Leili Tapak; Payam Amini; Azam Geravandi; Babak Moeini; Omid Hamidi; Maryam Afshari (Scientific Reports)
Abstract This study investigates factors influencing physical activity based on the Transtheoretical model (TTM) among adolescents. This study was conducted on 745 individuals between the ages of 12 and 16 years and was analyzed using a generalized linear model (GLM) approach with appropriate link functions using both classical and Bayesian frameworks. The results show that in model 1, the probit link function is a more appropriate approach to determine the risk factors for physical activity. In model 2, the logit link function is a more appropriate approach to determine the risk factors for physical activity. In addition, this study highlights a positive association between theatrical relief (OR = 1.08; 95% CI 1.02,1.14) and self-efficacy (OR = 1.06; 95% CI 1.02,1.09) for physical activity, and a negative association between self-relief (OR = 0.82; 95% CI 0.74,0.90), counter-conditioning (OR = 0.85; 95% CI 0.79,0.92), stimulus control (OR = 0.87; 95% CI 0.81,0.93) and helping relationships (OR = 0.94; 95% CI 0.88,0.99) with physical activity among female students. Self-efficacy is crucial for predicting activity levels, suggesting beneficial interventions that combine physical activity with self-efficacy enhancement. Positive thinking and a structured behavior change process are essential for physical activity engagement.